Identification of IPF specific genes expressed by lung tissue-derived fibroblasts using next generation sequencing - Seo, Eun-Jeong; Lee, Jong-Uk; Park, Seung-Lee; Kim, Min-Kyung; Choi, Jae-Sung; Hwang, Hun-Gyu; Kim, Jung-Hyun; Chang, Hun-Soo; Park, Choon-Sik (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2026)
Background and aim: Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease characterized by aberrant fibroblast activation and excessive extracellular matrix (ECM) accumulation, resulting in irreversible lung remodeling. Although fibroblasts are central to IPF pathogenesis, comprehensive transcriptomic analyses of IPF patient-derived lung fibroblasts remain limited. This study aimed to identify novel molecular contributors to IPF through transcriptomic profiling of lung fibroblasts.Methods: We performed total RNA sequencing on primary lung fibroblasts isolated from 33 IPF patients and 10 controls, the latter derived from histologically normal lung tissue adjacent to resected tumors. Differentially expressed genes (DEGs) were identified using trimmed mean of M-values normalization and the Exact test with Bonferroni correction. Gene ontology (GO) enrichment was conducted using DAVID, and network analyses were conducted via STRING and GeneClip3.Results: GO analysis of 475 DEGs (402 upregulated, 73 downregulated) revealed strong enrichment in ECM-related terms consistently observed across three prior IPF fibroblast datasets. Pathway analysis further implicated cytokine–cytokine receptor interaction, complement and coagulation cascades, and immune-related processes. Network analysis identified SERPING1, NR4A1, and C3 as shared hub genes across both STRING and GeneClip3 platforms. Of the top 20 DEGs, 15 had prior associations with fibrosis, while, six (HSD17B2, HMGCLL1, RASL12, HBG1, LOC105375566 and RIPOR3-AS1) were novel. OAS2, an interferon-stimulated gene, emerged as a novel immune-fibrotic axis component in IPF.Conclusions: This transcriptomic analysis confirms ECM dysregulation as a core feature of IPF pathogenesis and highlights novel DEGs and hub genes with potential roles in fibrosis, providing a foundation for future functional and translational studies.